(untitled) (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2022)
Scientific article entitled "THE INFLUENCE OF PROJECT TEACHING ON CREATIVITY AND ACHIEVEMENTS OF STUDENTS IN STUDYING SOCIAL CONTENTS WITHIN THE SUBJECT NATURE AND SOCIETY", authored by Aleksandar P. Janković, Andrijana Lj. Davidović and Dragan M. Lambić, published in issue 17 of the journal Sinteze - journal for pedagogical sciences, literature and culture, dated 10.12.2020, doi:10.5937/sinteze9-25402 and corections doi:10.5937/sinteze9-30998, is being retracted due to plagiarism.